A journey to disillusionment - Mazari, Sherbaz Khan. (Dhaka : University Press Limited, 2000)
Chronicle of political history of Pakistan; memoirs of a prominent Pakistani politician from 1964-1988.
"As told to Shehryar Khan Mazari"--T.p.
Includes bibliographical references and index.
BIED
Keywords: Mazari, Sherbaz Khan; Politicians -- Pakistan -- Biography; Pakistan -- Politics and government